PENINGKATAN HASIL BELAJAR IPA MATERI KENAMPAKAN RUPA BUMI MENGGUNAKAN MODEL SCRAMBLE - Ariyanto, Metta (Universitas Muhammadiyah Surakarta, 2016)
This study aims to improve understanding of the concept visual appearance of the earth through media-assisted learning model Scramble picture cards in Class III Elementary Negeri Sumogawe Getasan District of Semarang District 03 school year 2016/2017. The shape of this research is classroom action research (PTK) are conducted in two cycles. Each cycle consists of four phases: planning, implementation, observation, and reflection. Subjects were students in third grade students of SD Negeri 03 Sumogawe Getasan District of Semarang District, amounting to 34 students consisting of 17 male students and 17 female students. Source data comes from teachers and students. Data collection techniques used were interviews, observation, testing, and documentation. Results of research conducted initial conditions prior to student learning improvement achieve mastery only 15 students (46.42%), while 19 students (53.57%) have not yet reached the thoroughness with an average value of 61.42. In the first cycle has been implementing assisted learning method scrambe picture card games increased student learning outcomes that achieve completeness limit of 20 students (64.28%) and who have not completed 14 students (35.71%) with an average value of 63.57. At this stage of the second cycle of the 34 students who achieve mastery of 30 students (89.28%) who have not completed 4 students (10.71%) and the average value KKM science subjects is 65. Viewed from the repair cycle I and cycle II it can be concluded that this research is successful and does not need to continue the next cycle.